Biphase electrolyte and electrochemical device

By using two-phase electrolyte in aqueous zinc metal batteries, the spontaneous separation of the aqueous phase-organic phase is solved, and the corrosion caused by a single aqueous electrolyte and the slow ion transmission caused by a single organic electrolyte are solved, thus achieving the long-term battery life Cycle life and high capacity retention.

CN119447514AActive Publication Date: 2025-02-14TSINGHUA SHENZHEN INTERNATIONAL GRADUATE SCHOOL

Patent Information

Application Number
CN202411659493.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-14
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

In aqueous zinc metal batteries, a single aqueous electrolyte causes severe corrosion on the negative side of the zinc electrode and hydrogen evolution reaction, while a single organic electrolyte causes slow ion transmission kinetics, resulting in increased polarization of the battery and low Coulomb efficiency.

Method used

Provide a biphasic electrolyte that forms a stable layered aqueous phase-organic phase structure through spontaneous phase separation between water and organic solvents. It uses the differences in dielectric properties of organic solvents and the compatibility of water to optimize zinc deposition behavior and Form a stable solid electrolyte interface.

Benefits of technology

It effectively inhibits hydrogen evolution corrosion and dendrite growth, improves ion transfer rate and electrolyte conductivity, extends the cycle life of the battery and improves the capacity retention rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447514A_ABST
    Figure CN119447514A_ABST
Patent Text Reader

Abstract

The invention relates to a two-phase electrolyte and an electrochemical device, the two-phase electrolyte comprises an electrolyte salt, water and an organic solvent, the difference value of the Hildbrand solubility parameter of the water and the Hildbrand solubility parameter of the organic solvent is 13.5-15.3, and the relative dielectric constant of the organic solvent is 5-80. The water phase-organic phase in the double-phase electrolyte provided by the invention can realize spontaneous phase separation, and the double-phase electrolyte is a stable water phase-organic phase double-phase electrolyte, so that the problems of negative electrode hydrogen evolution corrosion, dendritic crystal growth and the like can be solved, and the ion transmission efficiency is improved; the battery using the two-phase electrolyte shows better long-term cycle life and high capacity retention rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a two-phase electrolyte and an electrochemical device. Background Art

[0002] Since non-aqueous electrolytes are not conducive to activating the lattice of transition metal oxides on the positive electrode side of zinc-ion batteries, the ion transport kinetics of zinc metal batteries are slow, which leads to problems such as increased battery polarization and low coulombic efficiency. In recent years, aqueous zinc metal batteries have attracted widespread attention and great development prospects due to their safety and environmental protection. The use of aqueous electrolytes can improve the ion transport of transition metal oxide positive electrodes, thereby improving the electrical performance of aqueous zinc metal batteries.

[0003] However, aqueous electrolytes are incompatible with zinc metal anodes and can easily induce severe hydrogen evolution reactions and dendrite growth, leading to energy loss and reduced efficiency of the battery. Summary of the invention

[0004] In view of this, in order to solve at least one of the above technical problems, the present application provides a self-phase-separating two-phase electrolyte.

[0005] In addition, the present application also provides an electrochemical device using the aforementioned two-phase electrolyte.

[0006] An embodiment of the present application provides a two-phase electrolyte, which includes: an electrolyte salt, water and an organic solvent, wherein the difference in Hildebrand solubility parameters between water and the organic solvent is 13.5~15.3, and the relative dielectric constant of the organic solvent is 5~80.

[0007] In some possible embodiments, the organic solvent is a hydrophobic aprotic halogenated solvent.

[0008] In some possible embodiments, the organic solvent includes at least one of fluoroethylene carbonate, N,N-dimethyltrifluoroacetamide, methyl trifluoroethyl carbonate, bis(2,2,2-trifluoroethyl) carbonate, chloromethyl ethyl carbonate and bis(2-chloroethyl) carbonate.

[0009] In some possible embodiments, in the electrolyte, the volume ratio of the water to the organic solvent is 1:(1-4).

[0010] In some possible embodiments, the electrolyte salt includes a hydrophilic zinc salt and an amphiphilic zinc salt.

[0011] In some possible embodiments, the hydrophilic zinc salt includes at least one of zinc sulfate, zinc chloride, zinc nitrate and zinc acetate; and / or The molar concentration of the hydrophilic zinc salt in the electrolyte is 0.5 mol·L-1 ~3mol·L -1 .

[0012] In some possible embodiments, the amphiphilic zinc salt includes at least one of zinc tetrafluoroborate, zinc trifluoromethanesulfonate and zinc bis(trifluoromethanesulfonyl imide); and / or The molar concentration of the amphiphilic zinc salt in the electrolyte is 0.5 mol·L -1 ~4mol·L -1 .

[0013] In some possible embodiments, the electrolyte further includes a salting-out agent.

[0014] In some possible embodiments, the salting-out agent includes at least one of aluminum sulfate, magnesium sulfate and ammonium sulfate; and / or The molar concentration of the salting-out agent in the electrolyte is 0.1 mol·L -1 ~4mol·L -1 .

[0015] An embodiment of the present application further provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet, a separator and the aforementioned electrolyte, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet.

[0016] Compared with the prior art, the biphasic electrolyte provided in the embodiment of the present application uses water and an organic solvent as solvents for the electrolyte salt, and limits the difference in the Hildebrand solubility parameters of water and the organic solvent to 13.5~15.3, and the relative dielectric constant of the organic solvent to 5~80, and utilizes the dielectric properties of the organic solvent and the difference in compatibility with water to achieve spontaneous aqueous-organic phase separation in the electrolyte, thereby achieving the construction of a stably stratified aqueous-organic biphasic electrolyte. In this electrolyte, the organic phase effectively suppresses problems such as hydrogen evolution corrosion and dendrite growth by optimizing the zinc deposition behavior on the negative electrode side and forming a stable solid electrolyte interface; at the same time, the aqueous phase promotes the ion transport kinetics on the positive electrode side, which is beneficial to the rapid transport and reaction of electrolyte ions. The electrochemical device using this electrolyte has a long cycle life and a high capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A schematic diagram of the structure of an electrochemical device provided in one embodiment of the present application.

[0018] Figure 2 This is a cycle life test chart of a Zn / / Zn symmetrical battery assembled using the electrolytes in Example 1 and Comparative Example 1 of the present application.

[0019] Figure 3This is a coulombic efficiency test graph of a Zn / / Cu asymmetric battery assembled using the electrolytes in Example 1 and Comparative Example 1 of the present application.

[0020] Figure 4 This is a test chart of the cycle performance of a Zn / / V2O5 full battery assembled using the electrolyte in Example 1 and Comparative Example 1 of the present application.

[0021] Figure 5 It is the non-in-situ electrochemical mass spectrometer of the Zn / / V2O5 soft-pack battery assembled using the electrolyte in Example 1 and Comparative Example 1 of the present application.

[0022] Figure 6 This is a deformation test diagram of a Zn / / V2O5 soft-pack battery assembled using the electrolyte in Example 1 of the present application.

[0023] Figure 7 This is a deformation test diagram of a Zn / / V2O5 soft-pack battery assembled using the electrolyte in Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0024] The following will clearly and completely describe the technical solutions in the embodiments of the present application in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments.

[0025] The inventors of the present application have found that in zinc ion batteries, a single aqueous electrolyte can cause severe corrosion and hydrogen evolution reaction on the zinc negative electrode side, a single organic electrolyte can lead to slow ion transfer kinetics, resulting in increased battery polarization and low coulombic efficiency, and the traditional two-phase electrolyte design can easily cause battery failure due to the metastable characteristics of the system, resulting in migration of the two-phase interface.

[0026] To this end, an embodiment of the present application provides a self-phase-separating two-phase electrolyte, which includes: an electrolyte salt, water and an organic solvent, wherein the difference in Hildebrand solubility parameters between water and the organic solvent is 13.5~15.3, and the relative dielectric constant of the organic solvent is 5~80.

[0027] Among them, the difference in Hildebrand solubility parameters between organic solvents and water is 13.5~15.3. The above difference indicates that the affinity between organic solvents and water is weak and the compatibility is poor, which can promote spontaneous phase separation in the electrolyte and is conducive to the formation of a water-organic phase dual-phase electrolyte with stable characteristics. When the above difference is too low (lower than 13.5), the organic solvent and water may be miscible to form a uniformly mixed solution, thereby lacking the ability to separate phases; when the above difference is too high (higher than 15.3), the interfacial tension between water and organic solvents may be too large. The difference in Hildebrand solubility parameters between organic solvents and water can further be 13.5~15.3, and can be exemplarily any value within the numerical range composed of 13.5, 14, 14.5, 15, 15.3 or any two of the above values.

[0028] The relative dielectric constant of the above-mentioned organic solvent is in the range of 5 to 80, so that the solvent can effectively dissolve the electrolyte salt and provide good ionic conductivity. The relative dielectric constant in the above range maintains the stable dissolution of the electrolyte salt in the organic solvent and promotes the effective transfer of ions between the aqueous phase and the organic phase. Combined with the difference in the Hildebrand solubility parameter between the organic solvent and water, the dissolution of the electrolyte salt further reduces the affinity of water and the organic solvent, thereby further promoting stratification, making it easier for the electrolyte to form a stable two-phase structure. When the relative dielectric constant of the organic solvent is too low (less than 5), it will affect the solubility of the salt in the organic solvent; when the relative dielectric constant of the organic solvent is too high (higher than 80), it may cause the interaction between the zinc ions and the solvent to be too strong, which is not conducive to the subsequent desolvation process, resulting in slow kinetics. The relative dielectric constant of the organic solvent can further be 5 to 80, and can be exemplarily any value within the numerical range composed of 5, 10, 20, 30, 40, 50, 60, 70, 80 or any two of the above values.

[0029] By introducing the above-mentioned organic solvent into the aqueous electrolyte, the suitable dielectric properties of the organic solvent and the difference in compatibility with water can be used to achieve spontaneous separation of the aqueous phase and the organic phase in the electrolyte, and the construction of a stable stratified aqueous phase-organic phase dual-phase electrolyte is achieved. In this dual-phase electrolyte, the organic phase effectively suppresses problems such as hydrogen evolution corrosion and dendrite growth by uniformly depositing zinc on the negative electrode side and forming a stable solid electrolyte interface, reducing gas production and capacity decay; at the same time, the aqueous phase promotes the ion transport kinetics on the positive electrode side, which is beneficial to the rapid transport and reaction of electrolyte ions and improves the reaction rate.

[0030] In some embodiments, the organic solvent may be a hydrophobic aprotic halogenated solvent. In addition to having a large Hildebrand solubility parameter difference with water, this type of organic solvent is also aprotic and does not participate in the migration or reaction of protons, which can further effectively inhibit the hydrogen evolution reaction and reduce gas generation.

[0031] In some embodiments, the organic solvent may include at least one of fluoroethylene carbonate, N,N-dimethyl trifluoroacetamide, methyl trifluoroethyl carbonate, bis(2,2,2-trifluoroethyl) carbonate, chloromethyl ethyl carbonate, and bis(2-chloroethyl) carbonate, etc. It is understood that the hydrophobic aprotic halogenated solvent includes but is not limited to the above solvents.

[0032] In some embodiments, the volume ratio of water to organic solvent in the dual-phase electrolyte can be 1:(1-4), further can be 1:(1-2), illustratively can be 1:1, 1:2, 1:3, 1:4 or any value within the numerical range formed by any two of the above values.

[0033] In some embodiments, the electrolyte salt may include a hydrophilic zinc salt and an amphiphilic zinc salt. The hydrophilic zinc salt is highly soluble in the aqueous phase, provides abundant zinc ions to the electrolyte, and improves the conductivity of the biphasic electrolyte. The amphiphilic zinc salt has a different distribution coefficient in the aqueous phase and the organic phase, so that a portion of the water is "captured" in the organic phase, so that the organic phase contains a small amount of water. The presence of a small amount of water in the organic phase helps to provide a good ion transfer channel, further improving the conductivity of the biphasic electrolyte.

[0034] In some embodiments, the hydrophilic zinc salt may include at least one of zinc sulfate, zinc chloride, zinc nitrate, and zinc acetate, etc. The above hydrophilic zinc salts all have good water solubility and can effectively provide zinc ions for the biphasic electrolyte.

[0035] In some embodiments, the molar concentration of the hydrophilic zinc salt in the biphasic electrolyte may be 0.5 mol·L -1 ~3mol·L -1 , which can be further 0.5 mol·L -1 ~1.5mol·L -1 , which can be 1 mol·L -1 , 2mol·L -1 , 3mol·L -1 Or any value within the numerical range formed by any two of the above values.

[0036] In some embodiments, the amphiphilic zinc salt may include at least one of zinc tetrafluoroborate, zinc trifluoromethanesulfonate, and zinc bistrifluoromethanesulfonyl imide.

[0037] In some embodiments, the molar concentration of the amphiphilic zinc salt in the biphasic electrolyte may be 0.5 mol·L -1 ~4mol·L -1 , which can be further 1 mol·L -1 ~3mol·L -1 , which can be 3 mol·L -1 , 1mol·L -1 , 2mol·L -1 , 3mol·L -1 , 4mol·L -1 Or any value within the numerical range formed by any two of the above values.

[0038] In some embodiments, the biphasic electrolyte may further include a salting-out agent. By adding a salting-out agent to the biphasic electrolyte, the water content in the organic phase can be adjusted so that the water content in the organic phase is maintained within a reasonable range, so that the zinc symmetric battery can achieve stable circulation, further promote the formation of a solid electrolyte interface, optimize the zinc ion deposition / stripping efficiency, and inhibit hydrogen evolution corrosion and dendrite growth.

[0039] In some embodiments, the salting-out agent may include at least one of aluminum sulfate, magnesium sulfate, and ammonium sulfate.

[0040] In some embodiments, the molar concentration of the salting-out agent in the biphasic electrolyte may be 0.1 mol·L -1 ~4mol·L -1 , which can be further 0.1 mol L -1 ~1 mol L -1 , which can be 0.1 mol·L -1 , 0.2mol·L -1 , 0.5mol·L -1 , 1mol·L -1 , 2mol·L -1 , 3mol·L -1 , 4mol·L -1 Or any value within the numerical range formed by any two of the above values.

[0041] Compared with the prior art, the biphasic electrolyte provided in the embodiment of the present application has the following beneficial effects: 1. The electrolyte is prepared by using an organic solvent with a Hildebrand solubility parameter difference of 13.5~15.3 with water and a relative dielectric constant of 5~80, which can form an interfacially stable water-organic dual-phase electrolyte, which can effectively inhibit problems such as hydrogen evolution corrosion and dendrite growth during charge and discharge, and increase the ion transfer rate and improve the conductivity of the electrolyte.

[0042] 2. Using amphiphilic zinc salt as part of the electrolyte salt so that the organic phase contains a small amount of water helps to provide a good ion transfer channel and further improve the conductivity of the biphasic electrolyte.

[0043] 3. By adding a salting-out agent, the water content of the organic phase can be precisely controlled to further reduce side reactions such as corrosion of the negative electrode, hydrogen evolution, and dendrite growth.

[0044] See also Figure 1 The embodiment of the present application also provides an electrochemical device 100, including a positive electrode sheet 10, a negative electrode sheet 20, a separator 30 and an electrolyte 40, wherein the electrolyte 40 adopts the aforementioned two-phase electrolyte. Specifically, the separator 30 is disposed between the positive electrode sheet 10 and the negative electrode sheet 20. Specifically, the electrochemical device 100 can be an aqueous zinc metal battery, the positive electrode sheet 10 can include a transition metal oxide positive electrode material, such as a vanadium pentoxide positive electrode material, and the negative electrode sheet 20 can be a zinc metal negative electrode.

[0045] The electrolyte 40 adopts the aforementioned two-phase electrolyte. Since the difference in the Hildebrand solubility parameters of the organic solvent and water in the two-phase electrolyte is 13.5~15.3, and the relative dielectric constant of the organic solvent is 5~80, the electrolyte spontaneously realizes phase separation, and a two-phase electrolyte of water phase-organic phase with stable stratification characteristics is obtained. In the electrochemical device 100, the organic phase on the negative electrode plate 20 side can optimize the zinc deposition behavior and form a stable solid electrolyte interface, effectively inhibiting problems such as hydrogen evolution corrosion and dendrite growth, thereby reducing the capacity attenuation and efficiency decline of the electrochemical device 100 caused by negative electrode damage, and reducing the generation of gas, thereby improving the safety of the electrochemical device 100. The aqueous phase on the positive electrode plate 10 side can promote the ion transfer kinetics, accelerate the rapid transfer and reaction of the two-phase electrolyte ions, and improve the charge and discharge capacity of the electrochemical device 100. Therefore, the electrochemical device 100 using the aforementioned two-phase electrolyte has a long cycle life and a high capacity retention rate. The application of the dual-phase electrolyte provided in the embodiments of the present application in a battery provides a new path for achieving a long-life aqueous zinc metal ion battery.

[0046] The above-mentioned two-phase electrolyte and electrochemical device are further described below through specific examples.

[0047] Example 1 The electrolyte includes electrolyte salt (hydrophilic zinc salt and amphiphilic zinc salt), salting-out agent, organic solvent and water. The hydrophilic zinc salt is zinc sulfate, the amphiphilic zinc salt is zinc trifluoromethanesulfonate, the salting-out agent is magnesium sulfate, the organic solvent is methyl trifluoroethyl carbonate, and the concentration of the hydrophilic zinc salt in the electrolyte is 1 mol·L -1 , the concentration of amphiphilic zinc salt is 1 mol·L -1, the concentration of salting-out agent is 0.5 mol·L -1 .

[0048] The specific preparation method comprises the following steps: Step S1, adding 287.56g of hydrophilic zinc salt zinc sulfate and 60.18g of salting-out agent magnesium sulfate into water, mixing evenly and then making up the volume to 1L with water to obtain an aqueous electrolyte.

[0049] Step S2, adding 363.53 g of amphiphilic zinc salt zinc trifluoromethanesulfonate to an organic solvent, mixing evenly, and then adjusting the volume to 1 L with an organic solvent to obtain an organic electrolyte.

[0050] Step S3, taking the same volume of the above-mentioned aqueous electrolyte and organic electrolyte respectively and placing them in a container, after sufficient stirring, the electrolyte self-separates into a stable aqueous phase-organic phase, and the electrolyte is a two-phase electrolyte with a stable interface phase.

[0051] Example 2 The difference between Example 2 and Example 1 is that the hydrophilic zinc salt selected in step S1 is zinc chloride, and the preparation method of the rest of the electrolyte is the same as that of Example 1, which will not be described in detail here.

[0052] Example 3 The difference between Example 3 and Example 1 is that the amphiphilic zinc salt selected in step S2 is zinc bis(trifluoromethanesulfonyl)imide, and the preparation method of the rest of the electrolyte is the same as that of Example 1, which will not be described in detail here.

[0053] Comparative Example 1 363.53 g of zinc trifluoromethanesulfonate was added to water, mixed evenly, and then the volume was adjusted to 1 L with water to obtain an aqueous electrolyte.

[0054] 1. The electrolytes obtained in Example 1 and Comparative Example 1 were subjected to the following tests: (I) The electrolytes prepared in Example 1 and Comparative Example 1 were applied to Zn / / Zn symmetrical batteries: The cycle performance of the Zn / / Zn symmetrical battery was simulated using a button cell CR2032 system, with the positive and negative effective areas of 1.13 cm 2 , take 100 μL of the organic phase in the dual-phase electrolyte of Comparative Example 1 or Example 1 to soak the glass fiber separator (membrane thickness is 675 μm), and when assembling the battery, stack them in the order of zinc foil, glass fiber membrane and zinc foil from top to bottom.

[0055] The Zn / / Zn symmetrical battery prepared above was subjected to constant current charge and discharge test to measure the cycle life of the battery. The test conditions were as follows: the current was 1 mA·cm -2 , capacity is 1 mAh cm -2 , that is, one cycle takes 2 hours, and the test results are as follows Figure 2 shown.

[0056] (II) The electrolytes prepared in Example 1 and Comparative Example 1 were applied to Zn / / Cu asymmetric batteries: The cycle performance of the Zn / / Cu asymmetric battery was simulated using a button cell CR2032 system, with the positive and negative effective areas of 1.13 cm 2 , take 100 μL of the organic phase in the dual-phase electrolyte of Comparative Example 1 or Example 1 to soak the glass fiber separator (membrane thickness is 675 μm), and when assembling the battery, stack the zinc foil, glass fiber membrane and copper foil in order from top to bottom.

[0057] The Zn / / Cu asymmetric battery prepared above was subjected to constant current charge and discharge test to measure the coulombic efficiency of the battery. The test conditions were as follows: the discharge current was 0.5 mA·cm -2 , the charging cut-off voltage is 0.5V, the test results are as follows Figure 3 shown.

[0058] (III) The electrolytes prepared in Example 1 and Comparative Example 1 were applied to Zn / / V2O5 full batteries: The cycle performance of the Zn / / V2O5 full battery was simulated using a button battery CR2032 system, in which the negative electrode was zinc foil, the positive electrode was V2O5, and the effective area of ​​the positive and negative electrodes was 1.13 cm 2 In comparative example 1, 100 μL of zinc trifluoromethanesulfonate electrolyte was dripped onto a glass fiber membrane (thickness 675 μm); in example 1, 50 μL of the aqueous phase in the two-phase electrolyte was dripped onto a glass fiber membrane (thickness 260 μm), and 50 μL of the organic phase in the two-phase electrolyte in example 1 was dripped onto a polypropylene separator (thickness 20 μm). The positive electrode was mixed into a slurry according to the mass ratio of active material: acetylene black: PVDF = 7:2:1, coated on a titanium foil, and dried in a blast drying oven at 80°C for 6 to 12 hours. When assembling the battery, the zinc foil, polypropylene separator, glass fiber membrane and positive electrode sheet were stacked in order from top to bottom.

[0059] The Zn / / V2O5 full cell prepared above was subjected to a constant current (2A·g -1 ) Charge and discharge test battery cycle performance, charge and discharge voltage range is 0.5V ~ 1.5V, test results are as follows Figure 4 shown.

[0060] (IV) The electrolytes prepared in Example 1 and Comparative Example 1 were applied to Zn / / V2O5 soft-pack batteries: The cycling performance of Zn / / V2O5 soft-pack batteries was simulated using an aluminum-plastic film bag battery system, in which the negative electrode was zinc foil with an effective area of ​​16 cm 2 , the positive electrode is V2O5, and the effective area is 12.25cm 2, Comparative Example 1 uses the prepared aqueous electrolyte, and the separator is a glass fiber membrane (thickness 675μm); Example 1 drips 250μL of the aqueous phase in the two-phase electrolyte onto the glass fiber membrane (thickness 260μm), and drips 250μL of the organic phase in the two-phase electrolyte onto the polypropylene separator (thickness 20μm). The positive electrode is mixed into a slurry according to the mass ratio of active material: acetylene black: PVDF = 7:2:1, coated on titanium foil, and dried in a blast drying oven at 80°C for 6 to 12h. When assembling the battery, stack them in the order of zinc foil, polypropylene separator, glass fiber membrane and positive electrode sheet from top to bottom.

[0061] The Zn / / V2O5 soft pack battery prepared above was subjected to a constant current (0.5 A·g -1 ) charge and discharge test, the charge and discharge voltage range is 0.5V ~ 1.5V, and the soft pack battery after cycle is subjected to non-in-situ electrochemical mass spectrometry test. The results are as follows Figure 5 As shown; the deformation of the soft pack battery after the cycle of Example 1 was measured, and the results are as follows Figure 6 As shown; the deformation of the soft pack battery after the cycle of comparative example 1 was measured, and the results are as follows Figure 7 shown.

[0062] The above results show that the cycle life of the Zn / / Zn symmetric battery assembled with the electrolyte in Comparative Example 1 is 90h, after which a short circuit occurs, the coulombic efficiency of the Zn / / Cu asymmetric battery is less than 85%, and the capacity of the Zn / / V2O5 full battery continues to decay during the cycle. Compared with Comparative Example 1, the cycle life of the Zn / / Zn symmetric battery assembled with the electrolyte in Example 1 is 1200h, the Zn / / Cu asymmetric battery can be stably cycled for 950 cycles, the average coulombic efficiency is greater than 99%, and the capacity of the Zn / / V2O5 full battery can be stably cycled for more than 3000 cycles. The battery assembled with the biphasic electrolyte in Example 1 has better cycle life, coulombic efficiency and capacity than the battery assembled with the aqueous electrolyte in Comparative Example 1 because the biphasic electrolyte simultaneously improves the side reactions on the negative electrode side of the battery and the ion transfer rate on the positive electrode side.

[0063] In addition, the Zn / / V2O5 soft-pack battery assembled with the electrolyte of Comparative Example 1 will produce a large amount of hydrogen after cycling, and the Zn / / V2O5 soft-pack battery will be severely deformed. Compared with Comparative Example 1, the gas production of the Zn / / V2O5 soft-pack battery assembled with the dual-phase electrolyte of Example 1 is significantly reduced, and the Zn / / V2O5 soft-pack battery does not undergo obvious deformation. This is because the dual-phase electrolyte is a water-organic dual-phase electrolyte with stable characteristics, and the side reactions such as negative electrode hydrogen evolution corrosion and dendrite growth are reduced. The battery using the dual-phase electrolyte exhibits good long-term cycle life and high capacity retention rate.

[0064] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A two-phase electrolyte, characterized in that: include: Electrolyte salt, water and an organic solvent, wherein the difference between the Hildebrand solubility parameters of water and the organic solvent is 13.5-15.3, and the relative dielectric constant of the organic solvent is 5-80.

2. The two-phase electrolyte according to claim 1, characterized in that The organic solvent is a hydrophobic aprotic halogenated solvent.

3. The two-phase electrolyte according to claim 1, characterized in that The organic solvent includes at least one of fluoroethylene carbonate, N,N-dimethyltrifluoroacetamide, methyl trifluoroethyl carbonate, bis(2,2,2-trifluoroethyl) carbonate, chloromethyl ethyl carbonate and bis(2-chloroethyl) carbonate.

4. The two-phase electrolyte according to claim 1, characterized in that In the two-phase electrolyte, the volume ratio of the water to the organic solvent is 1:(1-4).

5. The two-phase electrolyte according to claim 1, characterized in that: The electrolyte salt includes a hydrophilic zinc salt and an amphiphilic zinc salt.

6. The two-phase electrolyte according to claim 5, characterized in that: The hydrophilic zinc salt includes at least one of zinc sulfate, zinc chloride, zinc nitrate and zinc acetate; and / or The molar concentration of the hydrophilic zinc salt in the biphasic electrolyte is 0.5 mol·L -1 ~3mol·L -1 .

7. The two-phase electrolyte according to claim 5, characterized in that: The amphiphilic zinc salt comprises at least one of zinc tetrafluoroborate, zinc trifluoromethanesulfonate and zinc bis(trifluoromethanesulfonyl imide); and / or The molar concentration of the amphiphilic zinc salt in the biphasic electrolyte is 0.5 mol·L -1 ~4mol·L -1 .

8. The two-phase electrolyte according to claim 1, characterized in that: The two-phase electrolyte also includes a salting-out agent.

9. The two-phase electrolyte according to claim 8, characterized in that: The salting-out agent includes at least one of aluminum sulfate, magnesium sulfate and ammonium sulfate; and / or The molar concentration of the salting-out agent in the two-phase electrolyte is 0.1 mol·L -1 ~4mol·L -1 .

10. An electrochemical device, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet; wherein the electrolyte is a two-phase electrolyte as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Water / organic mixed electrolyte for zinc ion battery

    CN116130802A

  • Two-phase aqueous electrolyte and bipolar reaction environment-controllable aqueous battery

    CN117913382A

  • Zinc battery electrolyte, preparation method thereof and aqueous zinc battery

    CN117977016A

  • Two-phase electrolyte zinc ion battery

    CN118073672A

  • Electrolyte for metal zinc secondary battery

    JP2023127391A

Cited By

  • Dual-phase electrolyte for cooperatively regulating and controlling dual-electrode interface, preparation method of dual-phase electrolyte and zinc-manganese battery

    CN122267325A